COMPARATIVE STUDY OF MECHANICAL PROPERTIES, TPI, HAIRINESS AND EVENNESS OF CONVENTIONAL RING AND MODERN ROTOR SPUN YARN - Nakib Ul-Hasan; Farhana Afroz; Muhammad Mufidul Islam; S.M. Zahirul Islam; Rashedul Hasan (European Scientific Journal, ESJ, 2014)
This work presents a comparative study of the properties of yarns manufactured from identical raw material (100% cotton fiber), of 16 Ne & 20 Ne in conventional ring and modern rotor spinning frame. Mechanical properties e.g. tenacity, elongation%, TPI, hairiness and evenness e.g. unevenness, Thin/km, Thick/km, Neps/km, hairiness, CV of mass of both types of yarns were tested and compared. Ring yarns exhibit higher tenacity; where as rotor yarns expose better result in rest of the tests. Experimentally, most of the yarn characteristics are superior in rotor yarn, except tenacity; tensile strength of ring yarn is 36.36% higher than rotor yarn.